POTENTIAL USES OF THE PEEL AND SEED OF PASSIFLORA EDULIS SIMS F. EDULIS (GULUPA) FROM ITS CHEMICAL CHARACTERIZATION, ANTIOXIDANT, AND ANTIHYPERTENSIVE FUNCTIONALITIES - LAURA GONZÁLEZ; ANDREE ÁLVAREZ; ELIZABETH MURILLO; CARLOS GUERRA; JONH MÉNDEZ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Assess the performance of a crude ethanolic extract, a dichloromethane fraction and a hydroalcoholic residue, which are the basis for chemically and biologically characterizing the husk and seed of Passiflora edulis f. edulis, collected in the region and Colombia with a view to determining potential uses. Methods: Agroindustrial residues of gulupa (peel and seed) were analyzed through a bromatological study; subsequently, they were macerated with ethanol (96%). The crude ethanolic extract was partitioned with dichloromethane, leaving a hydroalcoholic residue. The content of total phenols, the composition of phytophenols (high-performance liquid chromatography-mass spectrometry), the total antioxidant capacity using 3-ethyl benzothiazoline-6-sulfonic acid (ABTS●+) and 2,2-diphenyl-1-pyridyl hydrazyl (DPPH●), the oxygen radical absorbance capacity (ORAC), and the ferric reduction power (FRAP) were determined to the extract, the fraction, and the residue. The evaluation of the inhibitory activity of the angiotensin-converting enzyme inhibitor (ACEI) and the cell viability assay with diphenyl bromide 3- (4,5-dimethylthiazole-2-) il) -2,5-tetrazolium on human leukocytes complemented the characterization. Results: Agroindustrial waste of P. edulis f. edulis, peel and seed, contains as main constituents: Protein (8.49 and 7.29%), fiber (34.2 and 55.7%), phosphorus (1.67 and 3.09), and boron (53.3 and 58.4 mg/kg), respectively. The seed showed 25.5% oil. The crude seed extract exhibited a higher phenolic content (15.34 gEAG/100 g). Likewise, it presented the highest antiradical capacity against ABTS●+ and DPPH● (706.17 and 82.81 trolox equivalent antioxidant capacity [TEAC], respectively) and antioxidant in ORAC and FRAP (142.79 TEAC and 103.63 equivalent ascorbic acid EAA, respectively). The ACEI activity (50% inhibitory concentration 17.62 mg/L) of the crude seed extract was higher than the other samples. No toxicity was found in the samples evaluated at concentrations higher than those of the biological activities manifested. Conclusion: The agroindustrial residues of P. edulis f. edulis (peel and seed) are rich in nutrients, which propose them for use in food matrices. The ethanolic extract from seed showed the highest antioxidant, antiradical, and inhibitory biological activity of the ACEI so that it could be proposed the gulupa seed as a promising phytotherapeutic product associated with its phenolic content, especially its flavonoids. The results obtained allow an added value to the fruit, reducing the chances that its waste contributes to environmental pollution.